THE EFFECT OF PRETREATMENT OF MICROWAVE HEATING ON EFFICIENCY OF HYDROLYSIS TIME AND α-CELLULOSIC CHARACTERISTICS OF PALM OIL WASTE BIOMASS - Fitriani Kasim; Khaswar Syamsu; Dwi Setyaningsih; Prayoga Suryadarma; Sudirman Sudirman (Jurnal Sains Materi Indonesia, 2018)
THE EFFECT OF PRETREATMENT OF MICROWAVE HEATING ON EFFICIENCY OF HYDROLYSIS TIME AND α-CELLULOSIC CHARACTERISTICS OF PALM OIL WASTE BIOMASS. This research is underlied by the needs of various industries for alpha cellulose, especially for the needs of raw material for cellulose nanocristalline, from fiber derived from the most potential waste biomass in Indonesia, namely oil palm empty fruit bunches (OPEFB) and mesocarp fibers. This study aims to find out the effect of pretreatment by microwave heating on the efficiency of hydrolysis time and alpha cellulose characteristics from palm oil waste biomass. To produce alpha cellulose, acid hydrolysis is commonly used with the multistage pulping process method, where the fiber is dissolved into HNO3 mixed acid, 3.5% and NaNO2, heated at a temperature of 90 oC for 2 hours, hydrolyzed and delignified to remove lignin and bleached, then separated from betha and gamma cellulose by dissolving it with NaOH 17.5%. In this study, a preliminary treatment (pretreatment) with microwave heating was carried out before the fiber was hydrolyzed so that the hydrolysis process was more efficient without reducing the characteristics of the alpha cellulose produced. The research results showed that pretreatment with microwave heating can streamline the hydrolysis time from 2 hours to 1 hour, without reducing its characteristics, where the degree of fiber crystallinity (XRD) and the yield of alpha cellulose remain high. Microwave heating with 450 watts for 5 minutes (treatment A) is better than 300 watts of heating for 10 minutes (treatment B). From the results of the study, it can be concluded that the pretreatment with microwave heating can streamline the hydrolysis time of the fiber to obtain alpha cellulose and increase the yield of the produced alpha cellulose.